C‐KIT‐ERK1/2 signaling activated ELK1 and upregulated carcinoembryonic antigen expression to promote colorectal cancer progression. Issue 2 (19th December 2020) - Ma, Jian; Liu, Xiaohui; Chen, Hong; Abbas, Muhammad Khawar; Yang, Liu; Sun, Haimei; Sun, Tingyi; Wu, Bo; Yang, Shu; Zhou, Deshan
Abstract: Carcinoembryonic antigen (CEA) is highly expressed in embryo and colorectal cancer (CRC) and has been widely used as a marker for CRC. Emerging evidence has demonstrated that elevated CEA levels promote CRC progression. However, the mechanism of the increased CEA expression in patients with primary and recurrent CRC is still an open question. In this study, we showed that c‐KIT, ELK1, and CEA were hyperexpressed in patients with CRC, especially patients with recurrent disease. From bioinformatics analysis, we picked ELK1 as a candidate transcription factor (TF) for CEA; the binding site of ELK1 within the CEA promoter was confirmed by chromatin immunoprecipitation and dual luciferase reporter assays. Overexpression of ELK1 increased CEA expression in vitro, while knockdown of ELK1 decreased CEA. Upregulated ELK1 promoted the adhesion, migration, and invasion of CRC cells, however knockdown of CEA blocked the activities of ELK1‐overexpressed CRC cells. Furthermore, we explored the role of c‐KIT‐ERK1/2 signaling in activation of ELK1. Blocking c‐KIT signaling using Imatinib or ISCK03 reduced p‐ELK1 expression and consequently decreased CEA levels in CRC cells, as did blocking the ERK1/2 pathway by U0126. Compared with wild type littermates, the c‐kit loss‐of‐functional Wads m/m mice showed lowered c‐KIT, ELK1, and CEA expression. In conclusion, our study revealed that ELK1, which was activated by c‐KIT‐ERK1/2 signaling, was a key TF for CEA expression. Blocking ELK1 or its upstream signaling could be an alternative way to decelerate CRC progression. Besides being a biomarker for CRC, CEA could be used for guiding targeted therapy. Abstract : Upon activation of c‐KIT signaling, downstream ERK1/2 and ELK1 are activated. p‐ELK1 elevates CEA transcription, which promotes CRC cell adhesion, migration, and invasion. Blocking ELK1 or its upstream signaling could be an alternative way to decelerate CRC progression.